Significance of youth and sports in Ukraine backup for the education of the younger generation - N. V. Tikhonova (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: determine the social significance and especially the development of youth and sports reserve in Ukraine. Material : a questionnaire survey of 50 experts in the sphere of physical culture and sports. Results : notes that children and youth and sports reserve three tasks: training of sports reserve, rehabilitation of children and youth, education of children and youth. Structure of youth and sports reserve in Ukraine in 1455 has youth sports schools, 184 specialized youth sports school of Olympic reserve, sports club 4522, 891 children and youth sports and sports club in the community population, 17 schools of Physical Culture and Olympic reserve, 35 high school sports. Conclusions : Children and Youth and reserve a sport that requires a thorough reform. Determined that develop youth sport must youth sports school.